Isolation and immunologic characterization of a human. B-lymphocyte- specific, cell surface antigen (The Rockefeller University Press, 1976)
In addition to HL-A antigens, another cell surface protein complex has been obtained from membranes of the human B-lymphoblast cell line IM-1. This complex which was solubilized with papain, consisted of polypeptides of 23,000 and 30,000 daltons (p23, 30). Rabbit antisera to this material precipitated from [35S]methionine-labeled detergent- solubilized cells, three proteins of 39,000, 34,000, and 29,000 daltons. These antisera were specifically cytotoxic for B lymphocytes of peripheral blood, for B-lymphoblast cell lines, and for EAC rosette receptor-positive surface Ig-negative (Null) lymphocytes. The p23,30 complex was not present on T lymphocytes, EAC rosette receptor-negative Null lymphocytes, or platelets. In addition, the p23,30 complex from several cell lines inhibited alloantisera from multiparous Amish women which had been shown to recognize non-HL-A, B-lymphocyte antigens. Some other properties of the anti-p23,30 sera antisera were described.